A DOM Tree Alignment Model for Mining Parallel Data from the Web - Shi, Lei; Niu, Cheng; Zhou, Ming; Gao, Jianfeng (COLING-ACL, 2005)
This paper presents a new web mining scheme for parallel data acquisition. Based on the Document Object Model (DOM), a web page is represented as a DOM tree. Then a DOM tree alignment model is proposed to identify the translationally equivalent texts and hyperlinks between two parallel DOM trees. By tracing the identified parallel hyperlinks, parallel web documents are recursively mined. Compared with previous mining schemes, the benchmarks show that this new mining scheme improves the mining coverage, reduced mining bandwidth, and enhances the quality of mined parallel sentences.